If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (W + -18)(w + 2) = 576 Reorder the terms: (-18 + W)(w + 2) = 576 Reorder the terms: (-18 + W)(2 + w) = 576 Multiply (-18 + W) * (2 + w) (-18(2 + w) + W(2 + w)) = 576 ((2 * -18 + w * -18) + W(2 + w)) = 576 ((-36 + -18w) + W(2 + w)) = 576 (-36 + -18w + (2 * W + w * W)) = 576 (-36 + -18w + (2W + wW)) = 576 Reorder the terms: (-36 + 2W + -18w + wW) = 576 (-36 + 2W + -18w + wW) = 576 Solving -36 + 2W + -18w + wW = 576 Solving for variable 'W'. Move all terms containing W to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 2W + -18w + 36 + wW = 576 + 36 Reorder the terms: -36 + 36 + 2W + -18w + wW = 576 + 36 Combine like terms: -36 + 36 = 0 0 + 2W + -18w + wW = 576 + 36 2W + -18w + wW = 576 + 36 Combine like terms: 576 + 36 = 612 2W + -18w + wW = 612 Add '18w' to each side of the equation. 2W + -18w + 18w + wW = 612 + 18w Combine like terms: -18w + 18w = 0 2W + 0 + wW = 612 + 18w 2W + wW = 612 + 18w Reorder the terms: -612 + 2W + -18w + wW = 612 + 18w + -612 + -18w Reorder the terms: -612 + 2W + -18w + wW = 612 + -612 + 18w + -18w Combine like terms: 612 + -612 = 0 -612 + 2W + -18w + wW = 0 + 18w + -18w -612 + 2W + -18w + wW = 18w + -18w Combine like terms: 18w + -18w = 0 -612 + 2W + -18w + wW = 0 The solution to this equation could not be determined.
| P+20=7 | | 4y-x-1x=5y | | x-100=62-8x | | G+13=19 | | 192=6r^6-1 | | 5x+6=6x-24 | | 3(17-x)=36 | | 4+3x-6=3+8x | | a×2/2=-7a | | 192=6z^5 | | 4x+15=6x+1 | | V-20=7 | | y=3-1/4x | | 2x+28=3x-8 | | -4x-9x=11/2 | | 15-6w=10w-21 | | -4x-5x=11/2 | | 8x-22=40 | | 5(3x+10)= | | 2(x+5)=54 | | 3x-25=x-7 | | 5x=2*3 | | -32=-4w | | 30+3x=30+6x | | 1/5(3x-1/2)-1/30=x/5 | | 7x+32=2(x-4) | | 5x=7*3 | | -6-1/1-2 | | 5x=2*5 | | 8x+2=3x-9 | | 4(u-6)=-9u-37 | | Y+6=22 |